Naprężenia w Otoczeniu Obwiedni Charakterystyk w Stanie Granicznym Ośrodka Sypkiego - Ostrowska, J.; Rychlewski, J. (Engineering Transactions, 1972)
The limit state of equilibrium of a granular medium is considered in the paper. In order to describe the state of stress in the neighbourhood of the characteristics envelope defined by its natural equations, the method of infinite power series with respect to the distance from the boundary is used. After changing the scale of infinitesimal magnitudes, the method makes it possible to derive simple recurrent formulae for the functional coefficients of the power series expansion of the state of stress. Two particular cases of perfectly cohesive media are presented, concerning a rectilinear and a circular arc boundary.